Does Accounting Quality Still Matter for Stock Price Crash Risk? Evidence from a High-Uncertainty Industry - Amanda Dwi Putri; Nikmah Nikmah (International Journal of Economics and Management Research, 2026)
This study examines the influence of accounting quality on stock price crash risk and investigates whether this relationship is conditioned by information asymmetry. Using a quantitative approach, this study utilizes secondary data derived from annual reports and stock price history of coal mining firms listed on the Indonesia Stock Exchange over the 2021–2024 period. Stock price crash risk is measured using negative conditional skewness (NCSKEW), accounting quality is proxied by discretionary accruals based on the Kothari model, and information asymmetry is captured through bid–ask spread. Panel data regression and moderated regression analysis (MRA) are applied to test the proposed relationships. The results indicate that accounting quality exhibits a negative but statistically insignificant association with stock price crash risk in the baseline specification. The moderated regression results further reveal a marginal moderating effect of information asymmetry, suggesting that the influence of accounting quality is conditional upon the firm’s informational environment. These findings highlight the context-dependent nature of accounting quality in explaining crash risk within high-uncertainty industries. This study contributes to the crash risk literature by providing evidence that accounting quality does not operate as a uniformly robust determinant of crash risk, while emphasizing the importance of broader informational conditions.